(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Alternate hemiplegia of childhood is a rare condition characterized by recurrent temporary episodes of hemiplegic attacks that affect one or the other side of the body. The clinical manifestations may begin at the neonatal period up to the age of 4 years. The reported prevalence is estimated at 1/100000 in children under 16 years old. There are, as of yet, no specific therapies that are uniformly effective in eliminating the episodes associated with AHC. AHC childhood can be correlated with Ayurvedic concept of Skandagraha. Here a case of 8 year old male child had come to our hospital with recurrent hemiplegic attacks having history of involuntary movements. At the end of 10days of IP treatment which included Panchakarma procedures along with internal medication resulted in 5-10% improvement in the overall effect of therapy. Followed by Shamanachikitsa 30-40% improvement was observed. Hence a humble attempt has been made to explore the case.